The Effect of Aqueous Extract of Cinnamon on the Metabolome of Plasmodium falciparum Using (1)HNMR Spectroscopy - Parvazi, Shirin (J Trop Med, 2016)
Malaria is responsible for estimated 584,000 deaths in 2013. Researchers are working on new drugs and medicinal herbs due to drug resistance that is a major problem facing them; the search is on for new medicinal herbs. Cinnamon is the bark of a tree with reported antiparasitic effects. Metabonomics is the simultaneous study of all the metabolites in biological fluids, cells, and tissues detected by high throughput technology. It was decided to determine the mechanism of the effect of aqueous extract of cinnamon on the metabolome of Plasmodium falciparum in vitro using (1)HNMR spectroscopy. Prepared aqueous extract of cinnamon was added to a culture of Plasmodium falciparum 3D7 and its 50% inhibitory concentration determined, and, after collection, their metabolites were extracted and (1)HNMR spectroscopy by NOESY method was done. The spectra were analyzed by chemometric methods. The differentiating metabolites were identified using Human Metabolome Database and the metabolic cycles identified by Metaboanalyst. 50% inhibitory concentration of cinnamon on Plasmodium falciparum was 1.25 mg/mL with p < 0.001. The metabolites were identified as succinic acid, glutathione, L-aspartic acid, beta-alanine, and 2-methylbutyryl glycine. The main metabolic cycles detected were alanine and aspartame and glutamate pathway and pantothenate and coenzyme A biosynthesis and lysine biosynthesis and glutathione metabolism, which are all important as drug targets.